Environmental Justice in Urban Sanitation Policy: Assessing Access, Governance, and Infrastructure Gaps in Rio de Janeiro - Maryann Schoenberg (Universitas Muhammadiyah Jakarta, 2026)
Urban sanitation is not only a technical service but also a question of public policy, social justice, and democratic governance. This article examines environmental justice in urban sanitation policy in Rio de Janeiro, Brazil, by assessing access, governance, and infrastructure gaps across the city. Although Rio de Janeiro has relatively high aggregate indicators for water supply and sewerage coverage compared with many Brazilian municipalities, these averages may conceal significant inequalities affecting low-income communities, favelas, peripheral neighbourhoods, and residents exposed to environmental health risks. Using a qualitative case-study design, this article analyses secondary data from national sanitation indicators, the Municipal Basic Sanitation Plan for Water and Sewerage of Rio de Janeiro, census-based information on favelas and urban communities, legal documents, and academic literature on environmental justice and sanitation governance. The findings suggest that Rio de Janeiro’s sanitation challenge is best understood as a multi-dimensional justice problem. First, access indicators have improved, but service regularity, water losses, sewerage quality, affordability, and local infrastructure conditions remain uneven. Second, governance has become more complex following regionalised concessions and the coexistence of multiple operators and regulators across planning areas. Third, infrastructure deficits are spatially and socially concentrated, especially in informal settlements and peripheral zones where sanitation, drainage, housing, and environmental risks overlap. The article argues that environmental justice requires more than expanding networks. It requires transparent monitoring, territorial prioritisation, social participation, affordability safeguards, and integrated planning between sanitation, housing, drainage, public health, and climate adaptation. The study contributes to public administration and environmental engineering debates by showing that equitable sanitation policy must bridge technical infrastructure with institutional accountability and recognition of vulnerable urban populations.